Verbal Warfare in the Polish Media: An Analysis Of Conceptual Metaphors In Political Discourse - Gieroń-Czepczor, Ewa (Research in Language, 2013)
Cognitive semanticists, especially George Lakoff and the Rockridge Institute, joined the analysts of political discourse in the 1990s. Much has been said about the metaphorical language of the US leaders, Bush and Obama, especially during the time of the War on Terror, and a range of conceptual metaphors have been pinpointed, such as THE STATE AS A PERSON, THE STATE AS THE FAMILY, THE USA AS A MORAL LEADER/DEFENDER OF THE JUST CAUSE, WAR AS MEDICINE, ARGUMENT IS WAR. Polish political discourse is, in contrast, largely focused on internal issues and debates. The resulting image of the nation and its aims, as found in official and unofficial statements made by the Polish government and parliamentarians portrays a pervading simplistic and dualistic picture of the nation and – more importantly – suggests that all aspects of politics evoke the imagery of war waged against all other parties involved. This study traces conceptual metaphors in a large corpus of material. The primary sources include interviews with politicians as well as texts written by journalists commenting on the Polish political scene and the latest developments. Another source is daily news on popular portals and online services of selected Polish dailies and magazines. All the materials cover a period between September 2011 and mid-January 2012. The outcome of the analyses of spoken and written data reveals that political, social and economic antagonisms are well fed by language which highlights dichotomies and depicts ‘the others’ as the source of all evil. The metaphorical language largely follows the patterns investigated and described by Lakoff, providing a wealth of material to support the claim that ARGUMENT IS WAR. In the light of the collected data, multiple ‘wars’ are in progress successfully generating language of conflict.